2013
DOI: 10.1021/jf402077g
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Brassica carinata Seed. 2. Carbohydrate Molecular Structure in Relation to Carbohydrate Chemical Profile, Energy Values, and Biodegradation Characteristics

Abstract: The objectives of this study were to investigate (1) the carbohydrate chemical profile, (2) the energy values, (3) the rumen neutral detergent fiber (NDF) degradation kinetics, (4) the carbohydrate-related functional group structural features using a Fourier transform infrared (FTIR) spectroscopic technique with attenuated total reflectance (ATR), and (5) the correlations between carbohydrate intrinsic structural features and nutritional profiles in three strains of Brassica carinata in yellow and brown seed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 24 publications
5
36
1
Order By: Relevance
“…Most strong correlations within the carbohydrate region were observed between CELC area and tdCP, tdNDF, TDN 3x , ME, and NE m with r = 0.67–0.85 and between TSCHO area with tdCP, TDN 1x , ME 3x and ME with r = 0.71–0.75. Our results were not fully in agreement with those found in previous works targeting Brassica carinata seed, oilseed meals and DDGS . The limited sample sizes ( n = 4–9) or relatively narrow variations existed in both spectroscopic and nutrient information in these studies might account for the inconsistent data.…”
Section: Resultscontrasting
confidence: 97%
See 4 more Smart Citations
“…Most strong correlations within the carbohydrate region were observed between CELC area and tdCP, tdNDF, TDN 3x , ME, and NE m with r = 0.67–0.85 and between TSCHO area with tdCP, TDN 1x , ME 3x and ME with r = 0.71–0.75. Our results were not fully in agreement with those found in previous works targeting Brassica carinata seed, oilseed meals and DDGS . The limited sample sizes ( n = 4–9) or relatively narrow variations existed in both spectroscopic and nutrient information in these studies might account for the inconsistent data.…”
Section: Resultscontrasting
confidence: 97%
“…Therefore, variation tendencies on peak height and area ratios were found to be various among the by‐product types with the exception of height ratios of SCHO peak 1:2, SCHO peak 1:CELC and area ratio of SCHO:CELC and TCHO:TSCHO which had no changes ( P > 0.05). These results demonstrated that the characteristics of inherent molecular structural makeup in the selected by‐products were not stable, which was in full agreement with previous studies targeting crop residues and Brassica carinata seeds …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations